The Al- Qurthubi's Interpretation Of The Wages Of Teaching The Qur'an In Al-Jami' Li Ahkam Al-Qur'an - Sofi'i, Shokhib (UIN Mataram, 2024)
Wages for teaching the Qur'an have been debated among Muslims. This study aims to find out how the rules of wages for teaching the Qur'an according to Al-Qurthubi in the book Al-Jami Li Ahkam Al-Qur'an. This research is a qualitative research in the form of a literature study where the primary data source comes from the book Al-Jami' Li Ahkam Al-Qur'an. The result of this study is that the wages of teaching the Qur'an are allowed according to Al-Qur'thubi and this is the majority of scholars. Al-Qurthubi explained that the government is obliged to help the welfare of teachers. Although the wages of teaching the Qur'an are allowed, Al-Qurthubi emphasizes to teach sincerely not just pursuing worldly rewards. What Al-Qurthubi explained about the wages of teaching the Qur'an is still relevant today.